Pre service teachers' voices while learning to teach: what can be learned from England? - Abd. Rahman, Fadzilah; Scaife, Jon; Yahya, Nurul Aini (Universiti Putra Malaysia Press, 2010)
An attempt to facilitate pre-service teachers learning, which is attuned with their learning needs, raises questions regarding how these pre-service teachers learn to teach. Learning to teach is developmental and it is a lifelong process; therefore, it puts heavy demands of cognitive, affective, and performance nature upon pre-service teachers (PSTs). In fact, it is a complex process as information which is useful to experienced teachers may not have the same value to beginners (Arends, 2004). An understanding of the process of learning to teach may help to clarify the role of teacher education programmemes especially at the pre-service level (Feiman-Nemser and Remillard, 1996). For instance, what do PSTs come to know about teaching and learning? How in the process of becoming teachers do PSTs replace notions about teaching and learning with practical knowledge of subject matter, pedagogy, learners, contexts, and learning that can inform their teaching judgments and actions? This paper discusses the findings from a study conducted at the Department of Educational Studies of a university in England. The study focused on how pre service teachers develop their knowledge of teaching throughout their teaching practice period. An in-depth semi-structured interview was carried out with the preservice teachers who were in their final semester of a one year postgraduate programme and at the time of the study, were in school experience (practicum) placements. Results were summarised into four main categories, namely pre-service teachers’ preparations of the lesson, expectations of the learning outcomes, reflections of their teaching and rooms for improvements. Understanding how pre-service teachers learn to teach would be a great help in designing teacher education programme effectively. The knowledge needed by the PSTs should be the guidelines in developing the curriculum of a teacher education programme.